Comparative study in the outcome of intramedullary nailing to plating for both-bone forearm fracture in early and mid-adolescent age group - Upendra Jung Thapa (Medical Journal of Dr. D.Y. Patil Vidyapeeth, 2018)
Objective: The objective of this study was to compare the outcome of intramedullary nailing to plating for both-bone forearm fractures in early and mid-adolescent age group. Design: This was a retrospective, comparative study. Methods: A total of 76 skeletally immature adolescents with a mean age of 12.5 years; range 10–17 years treated operatively for both-bone forearm fractures from 2012 to 2017. Patient with fixation of only one bone, hybrid fixation, bilateral forearm injuries, previous forearm injuries, Galeazzi, Monteggia and radial head fracture, underlying bone pathology, and fracture associated with neurovascular injury were excluded from the study. Intervention: Forty-six patients (mean age, 12.33 years) underwent intramedullary nailing and 30 patients (mean age, 12.77 years) underwent plating. Main Outcome Measure: Time to fracture union, magnitude and location of maximum radial bow (both as a percentage of radial length), forearm rotation, and complications. Results: The mean union time for nail was 7.86 weeks and for the plate was 7.33 weeks which showed no statistically significant differences between the groups for the union of fracture at 3 months (P = 0.780). There were no significant differences between the two groups for the value of maximum radial bow magnitude and its location (P = 0.60). The maximum radial bow magnitude was significantly different from normative values in both groups (P = 0.003 nail and P = 0.001 plate); however, no statistically significant differences for the location of maximum radial bow (P = 0.370 nail and P = 0.632 plate). There were no residual angulation, displacement, or malrotation. Nearly 88% of patients in both groups regained full forearm rotation. There were one major complication and seven minor complications in the intramedullary nailing group and one major complication in plating group. Conclusion: Based on similar functional and radiographic outcomes, intramedullary nail and plate fixation in early and mid-adolescent age group patients for both-bone forearm diaphyseal fractures are equally effective treatment.